2008
DOI: 10.1038/npp.2008.148
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence Why Paroxetine Dose Escalation is Not Effective in Major Depressive Disorder: A Randomized Controlled Trial With Assessment of Serotonin Transporter Occupancy

Abstract: Dose escalation is often used in depressed patients who fail to respond to standard doses of selective serotonin reuptake inhibitors, but clinical efficacy is equivocal. We aimed to reassess the efficacy of paroxetine dose escalation and quantify whether paroxetine dose escalation increases occupancy of the serotonin transporter (SERT) more than placebo dose escalation in a randomized controlled trial. We recruited 107 nonpsychotic, unipolar depressed outpatients (18-70 years; Hamilton Depression Rating Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 57 publications
6
41
0
3
Order By: Relevance
“…The mean patient age was 43.3 ± 2.0 years, and 59.6% of all participants were female. Six RCTs included exclusively outpatients [21,23,24,25,26,27]. Four studies were carried out in North America [21,22,23,27] and 3 in Europe [24,25,26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean patient age was 43.3 ± 2.0 years, and 59.6% of all participants were female. Six RCTs included exclusively outpatients [21,23,24,25,26,27]. Four studies were carried out in North America [21,22,23,27] and 3 in Europe [24,25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 7 included RCTs, 2 investigated pharmacotherapy with fluoxetine ( n = 448) [21,22], sertraline ( n = 272) [23,24], and paroxetine ( n = 146) [25,26], whereas 1 study examined duloxetine ( n = 255) [27] and maprotiline ( n = 87) [25]. In the individual trials, the number of participants ranged from 60 [26] to 371 [21] (mean = 151.0 ± 112.9 patients), and trial duration varied between 3 [25] and 8 weeks [27] (mean = 5.0 ± 1.6 weeks).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To some extent, pharmacoepigenetics inherits all hopes and expectations associated with pharmacogenomics; however, in contrast to pharmacogenomics, pharmacoepigenetics offers another level of understanding of different drug responses among individuals that cannot be explained by variation in DNA sequences [38]. Within the field of antidepressant response, some recent studies have shown that occupancy of the serotonin transporter is modified by 5-HTTLPR and is associated with the response to a SSRI [39,40,41]. Available data indicate that the single marker associations can account only for a small proportion of the variance in antidepressant response and indicate that multiple testing is required for reliable prediction [42].…”
Section: Discussionmentioning
confidence: 99%
“…Оптимизация дозиров-ки или увеличение продолжительности курса не различаются в баллах с аугментацией или комбини-рованной терапией, в то время как два последних метода предположительно более эффективны [22][23][24].…”
unclassified